On P- and p-Convexity of Banach Spaces - Omar Muñiz-Pérez (Abstract and Applied Analysis)
We show that every U-space and every Banach space X satisfying δX(1)>0 are P(3)-convex, and we study the nonuniform version of P-convexity, which we call p-convexity.